Study on the motor development and biomechanical characteristics of children aged 3–5 years - Hou, Bojie; Zhao, Jie; Ji, Zhongqiu; Jiang, Guiping; Song, Zhanbing (Frontiers in Public Health, 2025)
ObjectiveThis study analyzes changes in gait biomechanics in children aged 3–5, exploring motor development patterns during this critical period.MethodsUsing the BTS SMART DX infrared system and Kistler 3D force plate, three-dimensional gait motion and ground reaction forces were collected from 3-, 4-, and 5-year-olds during walking. Inverse dynamics analysis with Anybody 7.4 software provided detailed joint moments, muscle forces, and joint angles. Coordination patterns of joint angles and moments, Lyapunov exponents, muscle force data, joint energy absorption, and power were further analyzed.ResultsJoint angle coordination patterns remained consistent across ages, while joint moment control patterns simplified from three to two with age, indicating progressive joint control development. Muscle strength, joint power, and gait stability improved with age, reflecting enhanced movement efficiency and adaptability to complex motor tasks.ConclusionGait control in 3-year-olds is immature and mainly hip- and knee-dependent. At 4 years, children show significant joint coordination changes with increased ankle involvement, marking a transitional phase. By age 5, children exhibit more complex and stable gait control, though still developing. Overall, gait stability and coordination increase with age, with 4 years as a critical developmental period and 5 years showing more refined control characteristics.